Lessons from Transvaal House: Balancing Heritage, Culture and Sustainability - Victor, Andy (University of the Witwatersrand, Johannesburg, 2025)
This research report investigates Transvaal House, a modernist home designed by Stanley Saitowitz during apartheid, as a lens through which to explore architectural heritage, cultural identity, and sustainability in post-apartheid South Africa. The study situates the house within its historical, social and political context, examining its design influences, including modernist principles and vernacular elements, and its role in reflecting and resisting apartheid spatial planning. Using qualitative data drawn from site visits, informal discussions, and reflective analysis, the research addresses the building’s contested legacy and potential for adaptive reuse. Findings suggest that preserving Transvaal House facilitates critical conversations about history, race, and sustainability, transforming the building into a platform for inclusivity and learning. The research argues that Transvaal House’s contested legacy is its greatest strength, enabling critical engagement with South Africa’s architectural past while imagining a more inclusive and sustainable future.
A research report submitted in fulfillment of the requirements for the Master of Urban Studies in Sustainable Energy EƯicient Cities, in the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Transvaal House; Heritage, Culture and Sustainability; SDG-11: Sustainable cities and communities; SDG-12: Responsible consumption and production